Pengaruh Permainan Soccer Ball Bounce terhadap Keterampilan Passing Kaki Bagian dalam pada Pembelajaran Sepakbola - Kahan Tony Hendrawan; Novita Nur Synthiawati (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to examine the effect of the Soccer Ball Bounce game on students' inside foot passing skills in football. The study employed a quantitative approach using a quasi-experimental design with a one-group pretest-posttest design. The population consisted of all tenth-grade students at SMA PGRI Ploso, while the sample comprised 30 students from Class X-1 selected through cluster sampling. Data were collected using a psychomotor performance test. The results showed that the mean pretest score increased from 58.84 to 71.23 on the posttest. The paired t-test revealed a t value of 14.965, which exceeded the critical t value of 2.045 (df = 29, α = 0.05). These findings indicate that the implementation of the Soccer Ball Bounce game had a significant positive effect on students' inside foot passing skills among Class X-1 students at SMA PGRI Ploso.